Pengaruh Leverage, Ukuran Perusahaan dan Good Corporate Governance terhadap Tax Avoidance pada perusahaan Properti dan Real Estate - Ariani, Rosalia Indah (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2025)
This research aims to analyze the effect of leverage, firm size, and good corporate governance (GCG) on tax avoidance practices in property and real estate firms listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The study employs a quantitative approach using secondary data obtained from the firms’ financial statements. Data analysis is conducted using multiple linear regression and classical assumption tests. The results indicate that, simultaneously, leverage, firm size, and GCG significantly affect tax avoidance, with an R² value of 88.6%. However, in partial analysis, only the GCG variable has a significant effect on tax avoidance, while leverage and firm size do not show a significant influence. These findings underscore the importance of implementing GCG principles to minimize tax avoidance practices within corporate environments. It is hoped that this study can provide input for regulators and corporate management in formulating more transparent and accountable governance policies.